CORAL REEF COVER CONDITION AND ABUNDANCE OF REEF FISH OF THE POMACENTRIDAE FAMILY IN THE WATERS OF PAGANG ISLAND, PESISIR SELATAN REGENCY, WEST SUMATRA - Hidayat, Aga Azmi; Zulkifli, Zulkifli; Thamrin, Thamrin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Coral reefs play a crucial role in maintaining marine biodiversity by providing habitat and resources for various aquatic organisms, including reef fish from the Pomacentridae family. This study aims to determine the condition of coral reef cover, the abundance of reef fish from the Pomacentridae family, and the relationship between coral reef cover and the abundance of reef fish from the Pomacentridae family in the waters of Pagang Island. The study used the Underwater Photo Transect (UPT) method for coral cover analysis and the Underwater Visual Census (UVC) method for fish abundance data collection. The results showed that the average percentage value of coral reef cover at a depth of 5 m was 22.18%, and at a depth of 7 m was 12.80%, indicating a poor category for the percentage value of coral reef cover. Data collection was carried out at three different stations. The highest percentage of coral reef cover was found at station III at a depth of 5 m at 46.74% and at a depth of 6 m at 28.81%, while the lowest value was at station I at a depth of 5 m at 11.67% and at a depth of 7 m at 2.41%. The abundance of Pomacentridae reef fish varies between stations, with the highest abundance observed in areas with higher coral cover. Regression analysis showed a positive correlation between coral reef cover and fish abundance, indicating that declining coral reef conditions can have a negative impact on fish populations. These findings highlight the importance of coral reef conservation efforts to maintain marine biodiversity and ecosystem balance